2020
DOI: 10.1021/acs.jcim.0c00542
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Conventional Protein–Ligand Docking Software with Convolutional Neural Networks

Abstract: The high-performance computational techniques have brought significant benefits for drug discovery efforts in recent decades. One of the most challenging problems in drug discovery is the protein–ligand binding pose prediction. To predict the most stable structure of the complex, the performance of conventional structure-based molecular docking methods heavily depends on the accuracy of scoring or energy functions (as an approximation of affinity) for each pose of the protein–ligand docking complex to effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…If Tyr residue shows Fermi resonance in Raman spectra that gives an indication of the rotational degrees of freedom associated with the Tyr side-chain. 103 docking, [111][112][113] free energy calculations 114 (e.g. FEP, ABFE, MM/ PBSA or MM/GBSA) and biochemical assay can then be used to identify BACE-1 inhibitors (in broad sense this concept is applicable for other PAP inhibitors e.g.…”
Section: Ideal Playing Eld For Drug Repurposingmentioning
confidence: 99%
See 1 more Smart Citation
“…If Tyr residue shows Fermi resonance in Raman spectra that gives an indication of the rotational degrees of freedom associated with the Tyr side-chain. 103 docking, [111][112][113] free energy calculations 114 (e.g. FEP, ABFE, MM/ PBSA or MM/GBSA) and biochemical assay can then be used to identify BACE-1 inhibitors (in broad sense this concept is applicable for other PAP inhibitors e.g.…”
Section: Ideal Playing Eld For Drug Repurposingmentioning
confidence: 99%
“…Machine learning based methods ( e.g. convolutional neural network) combined with molecular docking, 111–113 free energy calculations 114 ( e.g. FEP, ABFE, MM/PBSA or MM/GBSA) and biochemical assay can then be used to identify BACE-1 inhibitors (in broad sense this concept is applicable for other PAP inhibitors e.g.…”
Section: Order Parameters To Capture Ligand Binding/unbindingmentioning
confidence: 99%
“…The graph coloring is based on Big-graph with the implementation in [82]. We used our own implementations for Bellman-ford and NN, and used the implementation of MedusaDock from [39]. Inputs: K-means uses three input images with different pixel diversities.…”
Section: Applications and Methodologymentioning
confidence: 99%
“…They found that the method performed consistently well in an inter-target pose prediction test, but it could hardly beat the classical Autodock Vina in an intra-target pose ranking test, which we are more concerned about. In 2020, Morrone et al proposed a dual-graph neural network model for pose prediction, which was concatenated by a ligand-only sub-graph to store ligand structures and an interaction-based sub-graph to represent protein–ligand interaction information [ 40 ]. Similarly, this model outperformed Autodock Vina in terms of the area under the receiver operating characteristic curve (AUROC) but did not show improved performance regarding the top 1 success rate.…”
Section: Introductionmentioning
confidence: 99%